Influence of Fasting Status and Sample Preparation on Metabolic Biomarker Measurements in Postmenopausal Women. - Neil Murphy; Roni T Falk; Diana B Messinger; Michael Pollak; Xiaonan Xue; Juan Lin; Robin Sgueglia; Howard D Strickler; Mia M Gaudet; Marc J Gunter (PLoS ONE)
Background Epidemiologic data linking metabolic markers-such as insulin, insulin-like growth factors (IGFs)-and adipose tissue-derived factors with cancer are inconsistent. Between-study differences in blood collection protocols, in particular participant's fasting status, may influence measurements. Methods We investigated the impact of fasting status and blood sample processing time on components of the insulin/IGF axis and in adipokines in a controlled feeding study of 45 healthy postmenopausal-women aged 50-75 years. Fasting blood samples were drawn (T0), after which subjects ate a standardized breakfast; subsequent blood draws were made at 1 hour (T1), 3 hours (T3), and 6 hours (T6) after breakfast. Serum samples were assayed for insulin, C-peptide, total- and free-IGF-I, IGF-binding protein [BP]-1 and -3, total and high molecular weight (HMW)-adiponectin, retinol binding protein-4, plasminogen activator inhibitor (PAI)-1, and resistin. Results Insulin and C-peptide levels followed similar postprandial trajectories; intra-class correlation coefficients [ICC] for insulin = 0.75, (95%CI:0.64-0.97) and C-peptide (ICC = 0.66, 95%CI:0.54-0.77) were similarly correlated in fasting (Spearman correlation, r = 0.78, 95%CI:0.64-0.88) and postprandial states (T1, r = 0.77 (95%CI: 0.62-0.87); T3,r = 0.78 (95%CI: 0.63-0.87); T6,r = 0.77 (95%CI: 0.61-0.87)). Free-IGF-I and IGFBP-1 levels were also affected by fasting status, whereas total-IGF-I and IGFBP-3 levels remained unchanged. Levels of adipokines were largely insensitive to fasting status and blood sample processing delays. Conclusion Several components of the insulin/IGF axis were significantly impacted by fasting state and in particular, C-peptide levels were substantially altered postprandially and in a similar manner to insulin.